Evolution of virulence in a novel family of transmissible mega‐plasmids. (24th May 2021) - Sitter, Thomas L.; Vaughan, Amy L.; Schoof, Marion; Jackson, Simon A.; Glare, Travis R.; Cox, Murray P.; Fineran, Peter C.; Gardner, Paul P.; Hurst, Mark R. H.
Summary: Some Serratia entomophila isolates have been successfully exploited in biopesticides due to their ability to cause amber disease in larvae of the Aotearoa (New Zealand) endemic pasture pest, Costelytra giveni . Anti‐feeding prophage and ABC toxin complex virulence determinants are encoded by a 153‐kb single‐copy conjugative plasmid (pADAP; a mber d isease‐a ssociated p lasmid). Despite growing understanding of the S . entomophila pADAP model plasmid, little is known about the wider plasmid family. Here, we sequence and analyse mega‐plasmids from 50 Serratia isolates that induce variable disease phenotypes in the C . giveni insect host. Mega‐plasmids are highly conserved within S . entomophila, but show considerable divergence in Serratia proteamaculans with other variants in S . liquefaciens and S . marcescens, likely reflecting niche adaption. In this study to reconstruct ancestral relationships for a complex mega‐plasmid system, strong co‐evolution between Serratia species and their plasmids were found. We identify 12 distinct mega‐plasmid genotypes, all sharing a conserved gene backbone, but encoding highly variable accessory regions including virulence factors, secondary metabolite biosynthesis, Nitrogen fixation genes and toxin‐antitoxin systems. We show that the variable pathogenicity of Serratia isolates is largely caused by presence/absence of virulence clusters on the mega‐plasmids, but notably, is augmented by external chromosomally encoded factors.